Working Paper 20: Corruption and human rights - Peters, Anne (Basel Institute on Governance Working Papers, 2015)
It is a fact that states with a high corruption rate (or a high corruption perception) are at the same time those with a bad human rights situation. Beyond this coincidence, the paper seeks to identify a concrete legal relationship between corruption and deficient human rights protection. This seems relevant and practical terms, because the extant international norms against corruption have so far yielded only modest success; their implementation could be improved with the help of human rights arguments and instruments. This paper therefore discusses a dual question: Can corrupt behaviour be conceptualised as a human rights violation? Should corrupt behaviour be categorised and sanctioned as a human rights violation? The author's answer is that such a juridic reconstruction is plausible under specific conditions, especially for petty corruption, but that we should be aware of the risks of such reframing of the issue.